Relationship between Students’ Emotional Intelligence and Their Tadarus Al-Qur’an Activities - Zaitun Syahbudin; Rita Ayu Muthia; Musa Thahir (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2019)
Emotional intelligence has been considered as contributing factor to students’ achievement in their academic life. Unfortunately, this intelligence seems to neglect on the part of students. In SMK (Sekolah Menengah Kejuruan/Vocational School) Negeri 2 Pekanbaru, students had religious program namely Tadarus Al-Qur’an from 2013 until now but this program contributes less to their emotional intelligence. This study is aimed at investigating the relationship between students’ participation in extracurricular activities of Tadarus Al-Qur’an with their emotional intelligence. This study was quantitative and it applied correlational method. Data were collected through questionnaires and 232 students participated in this study. The results were analyzed by product-moment correlation test and linear regression. The results showed that based on the grouping of students’ answer scores for emotional intelligence as follows: high group of 9.57%, medium group 69.57% and low group, 20.87%. This is based on the product-moment correlation test results and linear regression test results, both at the 5% level and at the 1% level. It can be concluded that there was a significant relationship between students’ participation in extracurricular activities Al-Qur’an and their emotional intelligence.